Patient and physician preferences for oral pharmacotherapy for overactive bladder: two discrete choice experiments. (2nd April 2016) - Heisen, M.; Baeten, S. A.; Verheggen, B. G.; Stoelzel, M.; Hakimi, Z.; Ridder, A.; van Maanen, R.; Stolk, E. A.
Abstract: Objective We examined patient and treating physician (general practitioners, urologists, and [uro]gynecologists) preferences for oral pharmacotherapy (antimuscarinics and beta-3 adrenoceptor agonists) for overactive bladder to gain a deeper understanding of which attributes drive their treatment decision-making and to quantify to what extent. Research design and methods Two separate discrete choice experiments were developed and validated using the input of patients and physicians. The patient experiment contained the following attributes: micturition frequency, incontinence, nocturia, urgency, dry mouth, constipation, increased heart rate, and increased blood pressure. The physician experiment contained two additional attributes: coping and atrial fibrillation. Both were fielded in five European countries. To allow for preference heterogeneity, utility functions were estimated using a mixed multinomial logit model. Results A total of 442 patient and 318 physician responses were analyzed. Patients ranked the attributes based on their largest potential impact on treatment value as follows: incontinence, nocturia, risk of an increased heart rate, urgency, frequency, risk of increased blood pressure, risk of constipation, and risk of dry mouth; and physicians as follows: incontinence, urgency, nocturia, frequency, risk of dry mouth, coping, risk of increased heart rate, risk of increased blood pressure, risk of atrial fibrillation, and risk of constipation. Conclusion and limitations In their valuations, physicians put more emphasis on increasing benefits, whereas patients put more emphasis on limiting risks of side effects. Another contrast that emerged was that patients' valuations of side effects were found to be fairly insensitive to the presented risk levels (with the exception of risk of dry mouth), whereas physicians' evaluated all side effects in a risk-level dependent manner. The obtained utility functions can be used to predict whether, to what extent, and for which reasons patients and physicians would choose one oral pharmacotherapy over another, as well as to advance shared decision-making.